Penerapan Pernyataan Standar Akuntansi Keuangan (PSAK) 45 Dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan - Ika Farida Ulfah; Ardyan Firdausi Mustoffa; Wijianto Wijianto (Jurnal Akuntansi dan Pajak, 2021)
Abstrak: Muhammadiyah Business Charity in the field of Education is a Charity Business which is engaged in Primary, Secondary and Advanced Education. Judging from the objective of a Muhammadiyah Business Charity in the Education Sector, it doesnnot seeknprofit or profit in carryingmoutnitsnfunctions, thenfoundation obtains fundsnfrom waqf, grants, donations and donations...from the community. Based ..on this, Muhammadiyah's Charity Business in Education has an obligation to be accountable andnreport the..funds used to related parties. The financial accountabilitymof an institutionnthat is not’ looking for profitnor profit must benprepared according to the..rules in accordancenwith the Financial Accounting Standards (SAK) and reinforced by the rules contained in the Statement of Financial..AccountingnStandards (PSAK) 45 which regulates the FinancialnReporting of Non-Profit Organizationsi. So it is necessary to apply PSAK 45 and Human Resources (HR) according to their competencies to be able to produce quality financial reports. The research methodnused is descriptivenanalytical method. The unitnof analysis for thisnresearch is the treasurer of TK / BA Muhammadiyah in Ponorogo Regency. The datanused are primaryndata. The sampling technique used saturated sampling. Thenstatistical analysist.used is multiple nregressiontanalysis. The results of this studynare: first, the implementation of PSAK 45 has a positive effectnon the qualitynof Aisyiyah's Kindergarten / BA Financial Report. Second, HR competencies have a positive effect on the quality of financial reports of TK / BA Aisyiyah and third, the implementation of PSAK 45 and HR competencies simultaneously have a positiveneffect on the qualitynof financialnreports.